PENGARUH PERSEPSI KEAMANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN UANG ELEKTONIK (STUDI KASUS PADA PENGGUNA APLIKASI E-WALLET DANA) - Marhaeni, Tri; Adiba, Farah; Anwariyah, Laili Rukhati (JOURNAL AKSES STIA MALANG, 2024)
The purpose of this research is to understand security perceptions and customer trust in influencing DANA e-wallet customer loyalty in the city of Malang. This type of survey research uses a quantitative approach, the sampling method used is purposive sampling because the sample is users of the DANA e-wallet application who have a transaction history using the DANA application, and the sample size is 100 people. The data collection method uses a questionnaire. Multivariate data analysis and using multiple linear regression and SPSS statistical tools. The results of the partial test research show that the trust variable influences and is clearly proven to influence loyalty. Meanwhile, the perception of security variable in transactions has not been proven to significantly influence loyalty. This is possible because the perception of transaction security is considered not to be the main factor in carrying out online transactions and consumers have made selective perceptions where they have modified the ideas and information messages they receive even though they conflict with the attitudes and beliefs they have learned. However, from the simultaneous test, the perceived security and trust variables have a positive and real proven effect on customer loyalty of the DANA E-Wallet application.